Utilizing Interactive Media to Enhance Arabic Literacy in Secondary School Students - Muhammad, Kemas; Irmansyah, Irmansyah (JURNAL IJ-ATL, 2024)
This study aims to explore the application of interactive media in improving Arabic literacy in secondary school students, focusing on the use of digital platforms and immersive technologies such as AR/VR. The research method used is a descriptive approach with qualitative analysis. The main findings indicate that the use of interactive media has a positive impact on improving students' understanding of Arabic vocabulary, grammar, and cultural context. However, challenges such as limited access to adequate technology and lack of training for teachers in integrating this technology into learning are still obstacles. This study also identified differences in students' comfort levels with technology, which affect the effectiveness of learning. Based on these findings, this study recommends increasing access to technology in schools, further training for teachers, and developing a curriculum that is more integrated with digital media. With these steps, it is hoped that Arabic language learning can be more effective and relevant to the needs of the digital era